2011
DOI: 10.1186/1472-6963-11-211
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of safety checklists for use by medical care teams in acute hospital settings - limited evidence of effectiveness

Abstract: BackgroundPatient safety is a fundamental component of good quality health care. Checklists have been proposed as a method of improving patient safety. This systematic review, asked "In acute hospital settings, would the use of safety checklists applied by medical care teams, compared to not using checklists, improve patient safety?"MethodsWe searched the Cochrane Library, MEDLINE, CINAHL, and EMBASE for randomised controlled trials published in English before September 2009. Studies were selected and appraise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 18 publications
1
97
0
1
Order By: Relevance
“…1,23,[25][26][27] Nevertheless, Ko et al's recent systematic review of checklist use in medicine has shown limited evidence of their effectiveness. 28 Analysis of the studies indicated that many were of poor quality with low levels of evidence and a high rate of bias. In summary, the authors determined that it was not feasible to provide an accurate summary of any trends across all studies.…”
Section: Discussionmentioning
confidence: 99%
“…1,23,[25][26][27] Nevertheless, Ko et al's recent systematic review of checklist use in medicine has shown limited evidence of their effectiveness. 28 Analysis of the studies indicated that many were of poor quality with low levels of evidence and a high rate of bias. In summary, the authors determined that it was not feasible to provide an accurate summary of any trends across all studies.…”
Section: Discussionmentioning
confidence: 99%
“…Effective checklist use, however, requires the perception that the organization embraces them (120). A growing body of evidence suggests that checklists can improve patient safety (73). Although commonly applied in intensive care units (12) and surgery (25,59), studies also describe checklist use in emergency departments, acute care settings, medication administration (44), and as part of multipronged programs (174).…”
Section: Coordinating At Care Transitions and Across Interdependent Fmentioning
confidence: 99%
“…Nevertheless, at least one study shows an inconsistent degree of effect on outcomes. 2 Others have investigated the impact of modifications of the SSC tailored to different clinical settings, as Morgan et al show in their study, ''Surgical safety checklist: implementation in an ambulatory surgical facility'' 3 , in this issue of the Journal.…”
mentioning
confidence: 99%